(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Ulcerative colitis is a most common form of inflammatory bowel disease (IBD) which mainly affect colon. The treatment of ulcerative colitis depends upon severity of the diseases. The aim of the present study was to determine the effect of hydroalcoholic extract of dried fruits of Helicteres isora in dextran sulfate sodium induced ulcerative colitis in experimental wistar rats. In this study wistar rats of either sex were divided into five experimental groups, where control group recived only distilled water. Group 2 was negative control group which received 4% dextran sulfate sodium (DSS) from drinking water between 15th to 21st day. Group 3 received low dose of hydroalcholic extract of Helicteres isora (HI) at a dose 100mg/kg orally along with 4% DSS from drinking water between from drinking water between 15th to 21st day. Group 4 received high dose of hydroalcholic extract of Helicteres isora (HI) at a dose 200mg/kg orally along with 4% DSS from drinking water between from drinking water between 15th to 21st day. In group 5 sulfasalazine was used as a standard drug at a dose 100mg/kg orally along with 4% DSS from drinking water between from drinking water between 15th to 21st day. Twenty four hours after treatment animals were sacrificed and further macroscopical, biochemical, histopathological evaluation was done and all the results were compare with control at p<0.05 significant value.